1592U89, a novel carbocyclic nucleoside analog with potent, selective anti-human immunodeficiency virus activity - Daluge, S M; Good, S S; Faletto, M B; Miller, W H; St Clair, M H; Boone, L R; Tisdale, M; Parry, N R; Reardon, J E; Dornsife, R E; Averett, D R; Krenitsky, T A (Antimicrobial agents and chemotherapy, 1997)
1592U89, (-)-(1S,4R)-4-[2-amino-6-(cyclopropylamino)-9H-purin-9-yl]-2-cyclo pentene-1-methanol, is a carbocyclic nucleoside with a unique biological profile giving potent, selective anti-human immunodeficiency virus (HIV) activity. 1592U89 was selected after evaluation of a wide variety of analogs containing a cyclopentene substitution for the 2'-deoxyriboside of natural deoxynucleosides, optimizing in vitro anti-HIV potency, oral bioavailability, and central nervous system (CNS) penetration. 1592U89 was equivalent in potency to 3'-azido-3'-deoxythymidine (AZT) in human peripheral blood lymphocyte (PBL) cultures against clinical isolates of HIV type 1 (HIV-1) from antiretroviral drug-naive patients (average 50% inhibitory concentration [IC50], 0.26 microM for 1592U89 and 0.23 microM for AZT). 1592U89 showed minimal cross-resistance (approximately twofold) with AZT and other approved HIV reverse transcriptase (RT) inhibitors. 1592U89 was synergistic in combination with AZT, the nonnucleoside RT inhibitor nevirapine, and the protease inhibitor 141W94 in MT4 cells against HIV-1 (IIIB). 1592U89 was anabolized intracellularly to its 5'-monophosphate in CD4+ CEM cells and in PBLs, but the di- and triphosphates of 1592U89 were not detected. The only triphosphate found in cells incubated with 1592U89 was that of the guanine analog (-)-carbovir (CBV). However, the in vivo pharmacokinetic, distribution, and toxicological profiles of 1592U89 were distinct from and improved over those of CBV, probably because CBV itself was not appreciably formed from 1592U89 in cells or animals (<2%). The 5'-triphosphate of CBV was a potent, selective inhibitor of HIV-1 RT, with Ki values for DNA polymerases (alpha, beta, gamma, and epsilon which were 90-, 2,900-, 1,200-, and 1,900-fold greater, respectively, than for RT (Ki, 21 nM). 1592U89 was relatively nontoxic to human bone marrow progenitors erythroid burst-forming unit and granulocyte-macrophage CFU (IC50s, 110 microM) and human leukemic and liver tumor cell lines. 1592U89 had excellent oral bioavailability (105% in the rat) and penetrated the CNS (rat brain and monkey cerebrospinal fluid) as well as AZT. Having demonstrated an excellent preclinical profile, 1592U89 has progressed to clinical evaluation in HIV-infected patients.